School Students' Attitudes and Perceptions towards Mathematics - Mahajan, Rekha (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
For over thirty years, researchers have been investigating students‘ attitudes and beliefs towards Mathematics. In the present study, 134 responses were received from Mathematics students studying from Class 6 to Class 12. Among them 21 responses were rejected and 113 responses were used for the study. Mathematics Attitudes and Perceptions Survey (MAPS) was used to understand the perception of the students‘ right at school level and guide them their true ability to undertake higher studies and to understand the difficulties faced by school children in understanding Mathematics.  Among the respondents under study 47 (41.6%) were male and 66 (58.4%) were female; 30 (26.6%) had received awards in Mathematics and remaining 83 (73.4%) did not get any such recognition. The educational status of father and mother was also important which was Doctorate/Post Graduation in 42 (37.2%) and 46 (40.7%), respectively. At least one graduate father and mother was 50 (44.2%) and 48 (42.5%), respectively. Statistically, more number of mathematics students were in ‗Growth mindset‘ (61.1%); ‗Real World‘ (77.9%); ‗Confidence‘ (57.5%); ‗Interest‘ (61.1%); and ‗Problem solving‘ (55.8%); while in case of ‗Sense making‘ (60.2%) and ‗Answers‘ (56.6%) are significantly below the Mathematics group average. The results indicated that most of the Mathematics students in school had attitude for Mathematics, persistence on problem solving especially their use in daily life and high motivation and interest in Mathematics. In case of ‗Interest‘ (40.7%) and ‗Sense making‘ (39.8%) were above 0.80 indicating high motivational interest in Mathematics and learning mathematics for understanding.   The correlation study among the components indicated strong correlation between age of students and class. A significant and positive correlation between component ‗Answers‘ with all others components except ‗Real World‘ and ‗Interest‘. ‗Sense Making‘ had significant and positive correlation with all other components. Similarly, ‗Persistence in problem solving‘ too had significant and positive correlations with all the components except ‗Real World‘. There is strong correlation among ‗Persistence‘, ‗Sense making‘, ‗Interest‘ and ‗Answers‘. The present study will help in identifying and guiding students to go for Mathematics based on their attitude and believes towards Mathematics.